THE IDEOLOGICAL DISTURBANCE OF VIETNAM CONFUCIANITY IN THE XVI-XVIII CENTURIES - Nguyen, a.D. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2017)
In the 16-18th centuries there was a large number of cardinal changes in the political and socio-economic life of Vietnam. Confucianism as a political doctrine proved powerless to ensure the stability of centralized power, its position and dogma were already unconvincing for the society. Since Confucian values lost their brilliance, therefore, Confucian scientists required some actions that could lead to the restoration of former positions and the role of Confucianism among the ruling elite of the feudal system and in the society of that era.